ESTELAS DE CHAVÍN: DOS AVES SAGRADAS EN EL MUSEO DE ARQUEOLOGÍA Y ANTROPOLOGÍA DE SAN MARCOS - Cabanillas, Virgilio Freddy (2013)
We account for the finding of pieces of Andean stone sculpture in a private collection of art, specifically two stelae fragments of the Chavin culture. After identification, the sculptures were donated to the Museum of Archaeology and Anthropology UNMSM.